7-3x=3(2x-4)

Simple and best practice solution for 7-3x=3(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=3(2x-4) equation:


Simplifying
7 + -3x = 3(2x + -4)

Reorder the terms:
7 + -3x = 3(-4 + 2x)
7 + -3x = (-4 * 3 + 2x * 3)
7 + -3x = (-12 + 6x)

Solving
7 + -3x = -12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
7 + -3x + -6x = -12 + 6x + -6x

Combine like terms: -3x + -6x = -9x
7 + -9x = -12 + 6x + -6x

Combine like terms: 6x + -6x = 0
7 + -9x = -12 + 0
7 + -9x = -12

Add '-7' to each side of the equation.
7 + -7 + -9x = -12 + -7

Combine like terms: 7 + -7 = 0
0 + -9x = -12 + -7
-9x = -12 + -7

Combine like terms: -12 + -7 = -19
-9x = -19

Divide each side by '-9'.
x = 2.111111111

Simplifying
x = 2.111111111

See similar equations:

| 30ln(x)=10x^2 | | 10x^2=30ln(x) | | 10x^2=30(lnx) | | 10x^2=30lnx | | 2x+2y=260 | | x^2-8x-89=0 | | Y=1750+0.8Y | | 500=8t^2+4t+400 | | z+3i=1 | | z+3i=0 | | X/6*2=11 | | (lnx)/(lnx)^2 | | 4x/9-(5x-2)/3=3x/2 | | x(130-x)=4125 | | 3x+5=28-2x | | x-x^2=130 | | 9x+11=4x+1 | | -5(n-5)+7(n+1)= | | 4(x-3)+2(x-1)= | | -10(a+3)+6a= | | 7c-15-5c+42= | | 12-2c=2whatisc | | 6(n+3)+2n= | | -7(y-11)= | | -5+6c-5c= | | 5(1+3x)=125 | | -3n+8+8n= | | 40h+25k+35= | | -8c+c= | | -3a+11a= | | 305=0.15x+16y | | 9=2y-(2y-9) |

Equations solver categories